Effectiveness, Teaching, and Assessments: Survey Evidence from Finance Courses - Lai M.M.; Kwan J.H.; Kadir H.A.; Abdullah M.; Yap V.C. (Taylor and Francis Ltd., 2024)
The present article examines the effectiveness, teaching, assessment methods, and the importance of finance concepts in three undergraduate finance courses in a private university in Malaysia. Approximately 224 undergraduates (finance majors) were surveyed and demonstrated positive attitudes toward the effectiveness of the finance subjects. The students indicated that the finance degree courses are able to produce analytical, computer, communication, interpersonal, and language skills for them. The chalk-and-talk lecture method and tutorial session are still the most important teaching methods of all. The risks and returns concept emerged as the most important finance concept among all. 2010, Copyright Taylor & Francis Group, LLC.